Using Educational Technology in Teaching Chemistry by Intermediate Stage Teachers in the Capital of Baghdad from their Principals' Point of View. - Abdel Hafez Salameh; Sawsan AlJanabi (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
This study aims at investigating the use of intermediate school teachers in the capital of Baghdad for educational technology teaching chemistry. To achieve the objectives of the study a questionnaire was developed. Both the validity and reliability of the questionnaire were confirmed. The questionnaire was designed to measure using educational technology by Chemistry teachers. The study sample consisted of (254) male and female principals, from the governmental middle schools, in the capital of Baghdad, by using simple random sample method. The study found that using of educational technology in teaching chemistry by intermediate stage teachers in the capital of Baghdad was moderate from their principals' point of view. There were no significant differences at (α ≥ 0.05) in the degree of using educational technology in teaching chemistry by intermediate stage by chemistry teachers from the principals' point of view attributed to sex or experience. There were significant differences at (α ≥ 0.05) in the degree of using educational technology in teaching chemistry by intermediate stage teachers, from principals' point of view attributed to training courses, in favor of those who participated in three training courses.